2022
DOI: 10.3389/fncel.2022.856512
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Japanese Encephalitis by Metagenomic Next-Generation Sequencing of Cerebrospinal Fluid: A Case Report and Literature Review

Abstract: Japanese encephalitis (JE) is an acute viral central nervous system disease, although less than 1% of patients infected with Japanese encephalitis virus (JEV) result in JE, which has an extremely poor prognosis. The Routine detection methods for JEV are time-consuming or limited by hospital conditions, therefore, need the quicker and sensitive techniques to detect JEV. Here, we reported a 14-year-old female who was admitted to our hospital with a severe fever, progressively headache and unconsciousness. Based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…74,75 The agnostic nature of this approach enables unexpected pathogens to be revealed including emerging viruses or divergent genotypes of known pathogens that evade directed assays. 76,77 Appropriate sample types include brain tissue or CSF (or blood or urine in particular circumstances) in the context of a suggestive clinical history. While expense and technical constraints dictate that metagenomics still largely functions as a research tool, future advances in the field including dedicated funding streams should see this approach adopted into mainstream diagnostics for cases of unexplained encephalitis.…”
Section: Metagenomicsmentioning
confidence: 99%
“…74,75 The agnostic nature of this approach enables unexpected pathogens to be revealed including emerging viruses or divergent genotypes of known pathogens that evade directed assays. 76,77 Appropriate sample types include brain tissue or CSF (or blood or urine in particular circumstances) in the context of a suggestive clinical history. While expense and technical constraints dictate that metagenomics still largely functions as a research tool, future advances in the field including dedicated funding streams should see this approach adopted into mainstream diagnostics for cases of unexplained encephalitis.…”
Section: Metagenomicsmentioning
confidence: 99%
“…Viral metagenomics has been of great value for confirmation of emerging or unknown viral agents in clinical samples with undetermined diagnosis and for viral discovery [9,10]. The major advantages of metagenomics include high specificity of viral identification and the unbiased nature of viral detection, which enables full annotation of all viruses present in the tested sample [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…However, clinical diagnosis of viral encephalitis in some patients is challenging due to the widespread use of antibiotics [2]. Numerous studies conducted globally and domestically [3] [4] have found that patients with viral encephalitis exhibit elevated levels of immunoglobulin (mainly IgG) in the cerebrospinal fluid (CSF) early in the disease course. Therefore, intrathecal synthesis of IgG serves as a valuable clinical indicator for the early diagnosis and differential diagnosis of viral encephalitis.…”
Section: Introductionmentioning
confidence: 99%